Operation and Control of Converter Based Single Phase Distributed Generators in a Utility Connected Grid (International Journal of Engineering and Computer Science, 2017)
The operation and control of converter based single phase distributed generators (DG) in a utility connected grid is proposed in this paper. A common utility practice is to distribute the household single-phase loads evenly between the three phases. The voltage unbalance between the phases remains within a reasonable limit. The single phase sources are operated to deliver available maximum power generated while the rest of the power demands in each of the phases are supplied by the utility (and if available, three phase DG sources). However, the voltage unbalance can be severe if single-phase rooftop mounted PVs are distributed randomly among the households. Moreover, there can also be single-phase nonlinear loads present in the system. The cumulative effect of all these will cause power quality problem on the utility side. The problem can be macabre if three-phase active loads (e.g., induction motors) are connected to the utility feeder